The acceptance of social networking technologies at KPJ Rawang specialist hospital / Noor Fadhilah Sulong @ Razak - Sulong @ Razak, Noor Fadhilah (2015)
This study aims is to examine the attitude of workers at KPJ Rawang Specialist Hospital on how they use social networking technologies at their workplace. Social networking technologies is defined as the communication methods that is used the World Wide Web as a platform for creating the community. The sample of this study is 40 respondents consists of 11 departments at KPJ Rawang Specialist Hospital, which are Administration, Talent Management, Laboratory, Rehabilitation, Pharmacy, Finance, Diagnostic Imaging, Information and Technology, Customer Service, Marketing, and also Cardiology & ENT department. However, there are only 34 respondents who answered to the questionnaires given. From the findings, I found that there a significant between attitude of workers towards social networking technologies between the factors such as Perceived Usefulness, Perceived Ease of Use, and Perceived Enjoyment.